Β‐catenin cancer–enhancing genomic regions axis is involved in the development of fibrolamellar hepatocellular carcinoma. Issue 10 (24th August 2022) - Gulati, Ruhi; Johnston, Michael; Rivas, Maria; Cast, Ashley; Kumbaji, Meenasri; Hanlon, Margaret A.; Lee, Sanghoon; Zhou, Ping; Lake, Charissa; Schepers, Emily; Min, Kyung‐Won; Yoon, Je‐Hyun; et al.
Abstract: Fibrolamellar hepatocellular carcinoma (FLC) is a disease that occurs in children and young adults. The development of FLC is associated with creation of a fusion oncoprotein DNAJB1‐PKAc kinase, which activates multiple cancer‐associated pathways. The aim of this study was to examine the role of human genomic regions, called cancer‐enhancing genomic regions or aggressive liver cancer domains (CEGRs/ALCDs), in the development of FLC. Previous studies revealed that CEGRs/ALCDs are located in multiple oncogenes and cancer‐associated genes, regularly silenced in normal tissues. Using the regulatory element locus intersection (RELI) algorithm, we searched a large compendium of chromatin immunoprecipitation–sequencing (ChIP) data sets and found that CEGRs/ALCDs contain regulatory elements in several human cancers outside of pediatric hepatic neoplasms. The RELI algorithm further identified components of the β‐catenin–TCF7L2/TCF4 pathway, which interacts with CEGRs/ALCDs in several human cancers. Particularly, the RELI algorithm found interactions of transcription factors and chromatin remodelers with many genes that are activated in patients with FLC. We found that these FLC‐specific genes contain CEGRs/ALCDs, and that the driver of FLC, fusion oncoprotein DNAJB1‐PKAc, phosphorylates β‐catenin at Ser675, resulting in an increase of β‐catenin–TCF7L2/TCF4 complexes. These complexes increase a large family of CEGR/ALCD‐dependent collagens and oncogenes. The DNAJB1‐PKAc–β‐catenin–CEGR/ALCD pathway is preserved in lung metastasis. The inhibition of β‐catenin in FLC organoids inhibited the expression of CEGRs/ALCDs‐dependent collagens and oncogenes, preventing the formation of the organoid's structure. Conclusion : This study provides a rationale for the development of β‐catenin‐based therapy for patients with FLC. Abstract : A fusion protein kinase DNAJB1‐PKAc is the main driver of adolescent liver cancer fibrolamellar HCC. Our paper presents molecular mechanisms by which this kinase causes FLC. We also provide evidence that the inhibition of DNAJB1‐PKAc‐beta catenin pathway could be considered as a therapy for FLC.image